The Loading Rate Effect on the Fracture Toughness of Marble Using Semicircular Bend Specimens. (13th October 2020) - Gong, Fengqiang; Wang, Yunliang; Wang, Shanyong
Abstract : A series of dynamic fracture experiments on semicircular bend (SCB) marble specimens were conducted to characterize the loading rate effect using the INSTRON testing machine and the modified SHPB testing system. The fracture toughness of the marble specimens was measured from a low loading rate to a high loading rate (10 -3 ~10 6  MPa·m 1/2 s -1 ). The results show that the fracture toughness will increase with the loading rate. Since the fracture toughness at a magnitude of 10 -3  MPa·m 1/2 s -1 is regarded as the static fracture toughness, the specific value of DI F f (the dynamic increase factor of fracture toughness) can be obtained at the other loading magnitudes from dynamic fracture tests. To describe the variation in DI F f from low to high loading rates, a new continuous model of DI F f was put forward to express the quantitative relation between the loading rate and rock dynamic fracture toughness. It is shown that the new DI F f model can accurately describe the loading rate effect on the dynamic fracture testing data for rock materials.